O USO E A APROPRIAÇÃO DA GAMIFICAÇÃO NA FORMAÇÃO DOCENTE INICIAL: POSSIBILIDADES, POTENCIALIDADES E LIMITAÇÕES - BUSSOLOTTO, LUIS EDUARDO (2023)
This research is part of the studies linked to the Distance Education and Digital Technologies Study Group - GEEaDTD, at the State University of Midwest - UNICENTRO, led by Prof. Dr. Jamile Santinello, a permanent faculty member of the Graduate Program in Education. Thus, the core of this research lies in the investigation of the use and appropriation of gamification in initial teacher education, highlighting the potentialities and limitations of this methodology, as well as the emergence of the study of this strategy in the formative process of future educators. Guided by the following research problem: How can the implementation of gamification in initial teacher education impact the performance and preparation of future teachers for the challenges of education in the digital era? The aim of this work is to highlight the use and applicability of gamification as a teaching and learning strategy critically, contextualizing its use during the teacher training process. Assuming specific objectives: (a) Investigate the central panoramas of the game and gamification phenomenon from a historical and conceptual perspective in the digital era, dialectically situating future students and teachers; (b) Demonstrate possible connections between gamification, technology, and education, listing the use and applicability of gamification as a teaching and learning strategy; (c) Conduct a field research on the use of gamification as an alternative teaching methodology with students and undergraduates in pedagogy. The methodological approach was undertaken through a literature review, addressing crucial topics of the theme, based on the following authors: Cunningham and Zichermann (2011), Csikszentmihalyi (1990; 2014), Lévy (1999; 2001), McGonigal (2011), McLuhan (1964), Prensky (2001), and Veen and Vrakking (2006), delimiting the research into topics relevant to the theme: (1) the temporal context of digital culture and its users; (2) the concept and characteristics of games in contemporary times and the emerging relationship between games, education, and gamification; (3) the intricacies of gamification and its prerogative for contemporary teacher education. Following the study, in its empirical phase, the course on gamification in initial teacher education will be presented. The extension course was theorized and directed to undergraduates in the Pedagogy program at the State University of Midwest-UNICENTRO in 2022 and aimed to teach and demonstrate the applicability of gamification as a specific, powerful, and transformative teaching and learning strategy. The results showed that course participants changed their view of gamification, gaining a deeper understanding of its potential and applicability in education. The research reflections also highlighted the importance of overcoming unpreparedness and biases regarding gamification. Additionally, it emphasizes the importance of exploring innovative approaches and educational strategies to meet the demands of the digital era and prepare future teachers for the challenges of the constantly evolving educational environment.